Refugee higher education: Contextual challenges and implications for program design, delivery, and accompaniment. (January 2016) - Crea, Thomas M.
Highlights: Refugees discuss their experiences in a hybrid higher education program. These experiences are compared with data provided by students on quality of life. Students are grateful for the opportunity but uncertain about the future. For marginalized populations, higher education may serve a psychosocial function. Principles of adaptive program design and delivery could strengthen the program. Program goals should be clearly articulated and linked to other supports. Abstract: Refugees experience limited access to adequate education at all levels but opportunities for higher education are especially lacking. This study explores the perspectives of 122 students involved in a pilot program of higher education in two refugee camps and one urban setting. Students reported gratitude for the experience but uncertainty about the future, and widely different contextual challenges to pursuing education. In a forced migration context, higher education may constitute a psychosocial intervention as much as an educational program. This unique dynamic begs the need for systemic thinking, with implications for program planning and delivery as a means of accompaniment.